Current Condition and Rules of Lean Implementation Practice in Agro-SMEs - Devi Maulida Rahmah; Totok Pujianto; Irfan Ardiansah (Universitas Padjadjaran, 2017)
This research aims to identify current condition and rules of lean manufacturing (LM) implementation in Agro- Small and Medium Enterprises (SMEs). The current condition aspects are identification of waste, LM techniques and methods, the reason and barriers on LM implementation in SMEs. Exploring the behavior of SMEs on implementing LM which supporting to generate productivity and efficiency on production system are important to be identified. Initially, LM concept are implemented in manufacturing industry especially in automotive industry. Nowadays this concept has been implemented by other sector included Small and Medium-size Enterprise. However, it has still a few number of Agro-SMEs implementing LM concept. The data from Indonesia Statistic revealed that the proportion of SME- agro based are in the total of SME in Indonesia. It insinuated that Agro-SMEs has a significant potency for national economic if their productivity increase. LM providing chance to improve productivity and efficiency in. Many research had conducted to explore LM implementation in various sector. Unfortunately, Research on LM implementation in Agro-SMEs has still a few number. Research was conducted in 12 Agro-SMEs around Sumedang and Bandung. Selected SMEs referring to the use of horticulture and plantation commodity as a raw material. The data collected by field observation and deep interview to the owner, management-level, and employer. The data presented through description of qualitative and quantitative analysis. The result shows that the motion becomes a dominant waste in SMEs at 30%, while over production activity contributes waste at 22%, waiting aspect at 17%, inventory at 13 %, defect and transportation at 9%. Motion generates negative impact to work productivity and effectivity, for instance increase of time consume unimportant activity at work, WIP of product, cost for labor, and cost production. In terms of Method and techniques implemented in Agro-SME, Continuous improvement (Kaizen) and 5 S outnumbered to other methods and techniques at 50%. Other method and techniques such as Teamwork and 5Why had contributed at 41.6%, TQM and Work standardization at 33.33%, and Jidoka at 16.67% as well as Kanban system, Value Stream Mapping (VSM), and SMED 0%. In terms of the reason on implementing LM, Improving the quality of product becoming a larger proportion which affecting the LM implementation at 36%. In other hand, knowledge outnumbered to others aspect. It contributes 35% as the most barrier factor on LM implementation.